The Hidden Nexus : A Case Report on the Interconnectedness of Metabolic Syndrome, Lifesyle, and Bilateral Nephrolitiasis - Kuntadi, Muhammad; Reilinvia, Shanine (Jurnal Ilmu Kedokteran Keluarga, 2025)
Chronic non-communicable diseases (NCDs) often share common root causes, necessitating a holistic approach to care. This report describes the case of a 42-year-old male presenting with bilateral nephrolithiasis. It refines the patient’s initial perception that his back pain was solely caused by hypertension, demonstrating instead that his condition is part of a broader metabolic dysfunction. A 42-year-old male presented with recurring right flank pain, diagnosed as bilateral nephrolithiasis. He had a history of hypertension, obesity (BMI 31.22 kg/m2), and hyperuricemia with gout. His mother also had a history of hypertension and nephrolithiasis. His lifestyle, including irregular eating habits, sedentary work, smoking, and a history of urine retention due to a demanding profession, along with a belief that medication is harmful to the kidneys, were key risk factors. The patient’s bilateral nephrolithiasis, likely uric acid stones given his history of hyperuricemia and gout, and hypertension are manifestations of an underlying metabolic syndrome. This condition, driven by obesity, lifestyle, and genetic predisposition, leads to low urinary pH, directly causing stone formation. This case illustrates the crucial role of a family-oriented approach in identifying and managing complex biopsychosocial barriers to care. This case highlights that managing chronic diseases effectively requires an understanding of their interconnectedness. A holistic family medicine approach, extending beyond symptoms to address lifestyle, psychosocial factors, and genetic risks, is essential for improving patient outcomes and preventing disease recurrence.